The Comparison of Under-Five-Children’s Nutrition Status Among Ethnic Groups in North of Iran, 1998 - 2013; Results of a Three Stages Cross-Sectional Study - Veghari, Gholamreza (Iran J Pediatr, 2015)
BACKGROUND: Despite improvements in child health, malnutrition still remains one of the main public health challenges in Iran. OBJECTIVES: The aim of this study was to compare under nutrition among under-five children with regard to ethnicity in rural area in north Iran. PATIENTS AND METHODS: In three cross-sectional studies 7575 subjects in three time-periods including 2339 children in 1998, 2749 in 2004, and 2487 in 2013, were evaluated. All under-five-children in 20 out of 118 villages were chosen by random sampling and assessed. Under nutrition was defined as underweight, stunting and wasting lower than -2 SD (Z < -2 SD). RESULTS: Generally, stunting was declined 17.1% and underweight and wasting were increased 0.9% and 1%, respectively during 15 years (1998 - 2013). Underweight increased 0.5% in Fars-natives and 3.2% in Turkmans and it was decreased 0.9% in Sistanis. Statistical difference in Turkman children among the three stages of the study was significant (P = 0.001). Stunting has decreased 28.7% in Fars-natives and 35.1% in Sistanis, it was increased 9.3% in Turkman group. Statistical differences among three stages in inter-ethnic groups were significant (P = 0.001 for all). Compared the group with good economic status, the odds ratio was 1.831 in poor economic group (P = 0.001). The risk of under nutrition in Sistanis was 1.754 times more than in Fars-natives (P = 0.001). CONCLUSIONS: Under nutrition remains one of the main health problems in under-five-year children in north Iran being more common in Sistani children. Stunting in Sistani children deeply decreased while in Turkman children slightly increased during the 15-year period study. Poor economic status is a risk factor for under nutrition in this area.